The effects of the elaboration likelihood model on initial trust formation in financial advisory services. Issue 3 (8th May 2018) - Silic, Mario; Ruf, Christian
Abstract : Purpose: In order for financial institutions to cope with increased competitive pressure from the financial technology companies, offering digital services such as a mobile service system (MSS) targeted for high net worth individuals (HNWIs) becomes critical. Despite long-term trustworthy relationships between HNWIs and financial advisors, studies suggest that the formation of initial trust poses a significant challenge. The purpose of this paper is to identify various features related to initial trust antecedents. Design/methodology/approach: The study was conducted using the survey data, and employs variance-based structural equation modeling (SEM) techniques to test hypotheses. Findings: The findings from a closed experiment with 107 participants suggest that compared to more traditional service systems, customers are more prone to the construct of service quality, and specifically professional, prompt, dependable and timely financial advice. Originality/value: The study validated key constructs that positively influence the initial trust formation process and ultimately the intention to use in an MSS for the financial advisory. The authorts particularly emphasized the rebalancing and monitoring steps in the financial planning process between HNWIs and client advisors.